Peningkatan Akurasi Penanganan Pengaduan Pelayanan Publik Berbasis Lokasi Pelapor Menggunakan Geolokasi - Basid, Puspa Miladin Nuraida Safitri A.; Nugroho, Fressy (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
The new normal era requires all activities to be online, so that people use more public services. However, at the same time the level of complaints has increased, from the many complaints that have been received, it must be known, which one is the correct complaint according to the location of the incident or is it just an act of ignorant hands. So that a special strategy is needed, by utilizing technology to determine the location of the incident accu-rately. One of the implementations of complaint handling by the whistleblower is that the reporter uses a smartphone. This is the reason the researchers raised the application of geotagging techniques to find out complete location information and geofencing methods to determine whether a location is included in the scope of an area. Several experiments have been carried out to test the accuracy of the techniques that will be applied to this e-complaint system. With an accuracy of 96%, this geofencing technique is good enough to be applied. In addition, the geotagging technique using EXIF from a digital image is considered the most suitable to be applied in this system than other geotagging techniques.